(3GdQbGHI Ydi GdCYeGd GdEOGQjI (B/s - (3YGWa, RGgQ YHO GdQMjes ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2009)
(3eGgjI GdEOGQI,GdQbGHI GdEOGQjI,COhGJ GdQbGHI GdEOGQjI,GdQbGHI Ydi GdCYeGd GdGOGQjI,GdQbGHI GdeGdjI GdYGeI,GdQbGHI hGdeJGHYI hGdJbjje,GdQbGHI GdOGNdjI Ydi GdeMGSHI,GdaSGO hcjajI GdQbGHI Ydjg,GdeSDhdjI GdGLJeGYjI aj GdCYeGd GdGOGQjI,CLgRI GdQbGHI GdOGNdjI hOjhGf GdNOeI GdeOfjI aj GdCQOfs
(3HHdjhZQGajG(B:(3U U(B.211-213s
Keywords: (3GdQbGHI GdEOGQjIs